Social media revolution and trends of da‘wah propagation in Ijebuland, Ogun State, Nigeria: An empirical survey - Kazeem Oluwaseun Dauda (Islamic Communication Journal, 2023)
Da‘wah plays a crucial role in spreading the teachings and principles of Islām globally. Different Islamic scholars have employed variety of techniques and platforms to fulfil this hallowed act of worship. Over the last two decades, social media revolution (SMR) has changed the dynamics of communication, democratized access to information, and promoted cross-cultural dialogue. Accordingly, Muslim preachers (Du‘āt) in Nigeria have considerably boosted their use of social media platforms, such as Facebook, X, Instagram, and YouTube, among others, for da‘wah. However, the extent to which SMR has influenced da‘wah activities in Ijebuland has received little attention in literature. This paper conducted an empirical survey into the impact of SMR on da‘wah propagation in Ijebuland, Ogun State. It used a descriptive survey design and content analysis approach. It argued that SMR has significantly changed the dynamics of da‘wah in the region. Despite the identified challenges facing their utilization, Ijebu Du‘āt have effectively utilized social media outlets with rational record of abuse. The study concludes that social media has indeed become a potent tool for da‘wah practice in Ijebuland. The findings justify the need for further studies to ascertain steps to take to strengthen SMR application to propagate da‘wah within the Islamic framework of tolerance, dialogue, mutual understanding and harmonious coexistence.***Dakwah memainkan peran penting dalam menyebarkan ajaran dan prinsip-prinsip Islam secara global. Berbagai cendekiawan Islam (ulama) telah menggunakan berbagai teknik dan platform untuk memenuhi ibadah suci ini. Selama dua dekade terakhir, revolusi media sosial (social media revolution/SMR) telah mengubah dinamika komunikasi, mendemokratisasikan akses terhadap informasi, dan mendorong dialog lintas budaya. Oleh karena itu, para pendakwah Muslim (du‘āt) di Nigeria telah meningkatkan penggunaan platform media sosial, seperti Facebook, X, Instagram, dan YouTube, antara lain, untuk dakwah. Namun sejauh mana pengaruh SMR terhadap kegiatan dakwah di Ijebuland hanya mendapat sedikit perhatian dalam literatur. Makalah ini melakukan survei empiris mengenai dampak SMR terhadap penyebaran dakwah di Ijebuland, Negara Bagian Ogun. Penelitian ini menggunakan desain survei deskriptif dan pendekatan analisis isi. Mereka berpendapat bahwa SMR telah mengubah dinamika dakwah di wilayah ini secara signifikan. Terlepas dari tantangan yang dihadapi dalam pemanfaatannya, para pendakwah Ijebu telah secara efektif memanfaatkan media sosial yang memiliki catatan penyalahgunaan yang rasional. Kajian tersebut menyimpulkan bahwa media sosial memang menjadi alat yang ampuh dalam praktik dakwah di Ijebuland. Temuan ini membenarkan perlunya studi lebih lanjut untuk memastikan langkah-langkah yang perlu diambil untuk memperkuat penerapan SMR guna menyebarkan dakwah dalam kerangka toleransi, dialog, saling pengertian dan hidup berdampingan secara harmonis dalam Islam.